Deseo, lenguaje, moral : perspectiva picoanalítica (2015)
ABSTRACT: This paper is part of the research "On Excess and Its Regulation. Reflections from Psychoanalysis and Philosophy”, carried out by the Psicoanálisis, Sujeto y Sociedad [Psychoanalysis, Subject and Society] research group, University of Antioquia, Colombia. Kant's theory of desire –named by him as "faculty of desire"– and Sigmund Freud's "experience of satisfaction" are here compared. These are two approaches to desire, the former coming from Philosophy, the latter from clinic. In relation to language, Jacques Lacan's logic of signifier is here presented together with the consequence of the emergence of an unconscious subject –subject considered by Lacan as a response of the Real. In relation to morals, the theory of superego and guilt is presented as a genesis of the Freudian morals.